Innovación tecnológica y su impacto en la gestión pública del gobierno autónomo descentralizado de quevedo, año 2022. - Contreras Barros, Michelle Guisella (2023)
The objective of this research is to evaluate technological innovation and its impact on the public management of the Decentralized Autonomous Government of Quevedo. As a methodology, a descriptive approach was used with application of field observation, a non-experimental design was applied with a hypothetical method for the object of study; The study population was the administrative staff of the GAD of the canton where the perception of 26 members of the institution was taken for the application of a survey on management, processes and use of technology and technological tools. With the results, the importance of the use of technologies in administrative management can be evidenced, the purpose of which is to redefine the processes, internal policies for the proper use of information and communication technologies, directly impacting what the Municipality of Quevedo does. It is evident that updated technological tools are not applied in administrative management, which makes the proper performance of daily activities difficult. It was concluded that the GAD Quevedo uses obsolete technological tools, there is a lack of platforms for users, lack of acquisition of technological equipment for the good and development of activities, technology is seen as a weapon of competition and, as such, it should be a key component of short and long term strategic planning.